David Hume’s Account of Justice - Enes Eryılmaz (İnsan & Toplum)
In this study, Hume’s theory of justice is examined critically with respect to morality, politics, and society. In addition to that, Hume’s account of justice is questioned owing to the free rider problem. First, the relationship between morality and justice is investigated. Although Hume takes sympathy seriously in his early works, he does not take sympathy to be a sure foundation in his later works. Then, circumstances of justice are explained to find exact place and necessity of the virtue of justice. With the way of deconstruction, Hume shows the cases that the virtue of justice is needed. Justice is largely concerned with the environment and dispositions of persons. Next, the artificial character of justice will be explained. Then, Hume’s laws of justice will be given and assessed: stability of property, exchange of property by agreement, and performance of promises. It is argued that Hume’s laws of justice mostly relate to economic justice. The chief drive that causes individuals to act justly is disciplined self-interest. Self-interest should be organized for public utility. Laws of justice are created by human conventions. The primary sources of the investigation are: Hume’s A Treatise of Human Nature, [1739] 1978; An Enquiry Concerning the Principles of Morals, [1751] 1998 and Political Essays, 1994.